3D numerical investigation of a free-burning argon arc with metal electrodes using a novel sheath coupling procedure. (13th November 2019) - Liang, P; Trelles, J P
Abstract: A novel coupling procedure describing the complicated plasma-electrode interaction process has been developed and applied into the 3D finite volume simulation of a direct current tungsten inert gas welding system. This is achieved by making the space charge layer (sheath) incorporated into the computation domain and interact with both bulk plasma and cathode through the effective electrical conductivity. Both chemical and thermal nonequilibrium phenomena as well as the self-induced magnetic fields have been taken into consideration by the model to ensure a realistic numerical description of a non-thermal arc. The applicability of this coupling procedure is further improved by calculating the real electric potential, which is capable of accounting for the effects of the complicated drift and diffusion processes. Numerical results of both 100 and 200 A discharge currents are presented, field reversal is obtained at near-anode regions in both cases, which is followed by the negative anode sheath potential drop. The region of the strongest electron overpopulation appears at the intersection of plasma fringes and electrode surface. Numerical results of plasma temperature and voltage show good agreement with experimental measurements.